The Arabidopsis Exine Formation Defect (EFD) gene is required for primexine patterning and is critical for pollen fertility. Issue 1 (3rd April 2014) - Hu, Jun; Wang, Zhaodan; Zhang, Liyao; Sun, Meng‐xiang
Summary: Exine, the outermost layer of a pollen grain, has important roles in protecting microspore cytoplasm and determining species‐specific interactions between pollen and stigma. The molecular mechanism underlying pollen exine formation, however, remains largely unknown. Here, we report the characterization of an Arabidopsis male‐sterile mutant, efd, which exhibits male sterility in first‐forming flowers. The Exine Formation Defect ( EFD ) gene is strongly expressed in microsporocytes, tetrads and the tapetum, and encodes a nuclear‐localized de novo DNA methyltransferase. Detailed observations revealed that EFD is involved in both callose wall and primexine formation during microsporogenesis. Microspores in tetrads are not well separated in efd due to an abnormal callose wall. Its plasma membrane undulation appears normal, but primexine patterning is impaired. Primexine matrix establishment and sporopollenin accumulation at specific positions are disturbed, and thus exine formation is totally blocked in efd . We confirmed that EFD is required for pollen exine formation and male fertility via the regulation of callose wall and primexine formation. We also found that positional sporopollenin accumulation is not involved in regulating membrane undulation, but is related to the complete separation of tetrad microspores during primary exine patterning.